Effects of d-cloprostenol administrations with 7.5 and 11.5-day intervals between administrations on pregnancy rates after artificial insemination in estrous cyclic dairy goats - Bonato, G. C.; Maia, A. L. R. S.; Cortes, L. R.; Oliveira, T. A.; Arrais, A. M.; Figueira, L. M.; Oliveira, M. E. F. [UNESP]; Souza-Fabjan, J. M. G.; Fonseca, J. F. (Elsevier B.V., 2019)
This study was conducted to evaluate effects of two administrations of d-cloprostenol at different intervals to synchronize the time of estrus and ovulation among estrous cyclic goats. In Experiment 1, 32 does were treated with 30 mu g d-cloprostenol at 7.5 (T7.5, n = 16) or 11.5-day (T11.5, n=16) intervals. In Experiment 2, the same treatments were administered and there was AI of the does (T7.5, n = 40 and T11.5, n = 38). In Experiment 1, ultrasonic assessments of ovaries were conducted at the time of the second administration of d-cloprostenol, every 12 h until detection of ovulation, and 7 days after estrous onset to detect the corpora lutea, as well as for pregnancy diagnosis 40 days after AI. In Experiment 1, the estrous response (90.6%, 29/32) was similar (P > 0.05) in both groups. Diameter of the largest follicle at the time of administration of the second dose was larger (P = 0.01) in the T7.5 than T11.5 group (7.0 compared with 5.7 mm), while the values for ovarian variables were similar (P > 0.05). In Experiment 2, the greatest (P < 0.001) synchrony in timing of initiation of estrus in does (T7.5 = 83.3% and T11.5 = 50.0%) occurred after the second day (36-48 h). The pregnancy rate tended (P = 0.0836) to be greater for does in the T7.5 (71.4%, 40/56) than T11.5 (55.6%, 30/54) group. With use of both protocols, there were acceptable estrous synchronization and pregnancy rates in estrous cyclic dairy goats.
Keywords: PGF2 alpha; AI; Estrous synchrony; Ultrasonography; Ovulation; Goats